Fictions of God: English Renaissance literature and the invention of the Biblical narrator - Magarik, Raphael ca. 20./21. Jh. (Class 200: new studies in religion, 2025)
"Literary histories often tie unreliable narrators, free indirect style, and even fiction itself to the rise of the novel in the eighteenth century. In The Invention of the Biblical Narrator, Raphael Magarik argues these forms emerged two centuries earlier, amid the religious upheaval of the Reformation. The Reformation, Magarik says, was not a time of plain-sense Protestantism, but rather one where thinkers newly read the Bible as containing fallible, human narrators who shaped scriptural stories' perspective and style. Early reformers found such narrators in the Bible because of a divine counterfactual: that God crafted the texts as if they were written by people like Moses or Isaiah. The Invention of the Biblical Narrator traces how literary form passed from theologians and commentators like Martin Luther and John Calvin to poets like Abraham Cowley, John Milton, and Lucy Hutchinson. Reading Protestant theological treatises and commentaries, Renaissance world histories and biblical epics together with the history of the emerging secular state and contemporary post-secular critique, Magarik connects narratology and theology to Reformation writers' negotiation of religious-political struggle. It was during this violent creation of secular states that Renaissance English writers found in their Bibles not dogma, but fiction, and they experimented with their own ironized narrators"--